Evaluating the benefits of legacy phosphate - Barrow, N. J.; Roy, Dibakar; Debnath, Abhijit (Plant and soil, 2022)
Aims Many soils in the developed world have been fertilized with phosphate for several decades. Appreciable phosphate has accumulated in such soils. This is referred to as “legacy P”. The benefits of legacy P are not widely appreciated. Here, we report the effects of legacy P on buffering capacity and the consequent effects on the effectiveness of plant growth, and its effects on the continuing reaction between soil and P and the consequent effects in decreasing the decline of P effectiveness with time. Methods We produced five levels of legacy P by incubating the soil with added phosphate at high temperatures for 30 days. We then measured the effect on sorption/desorption and on plant growth in response to further additions of phosphate. Results Legacy P decreased soil buffering capacity, decreased hysteresis of desorption, and increased the amount of P in a similar state to that of the recently sorbed P. There were analogous effects of plant growth; effectiveness of P fertiliser increased; the decline in effectiveness with time decreased; and the amount of soil P accessible to plants increased. We think that soil tests reflect only the amount of soil P accessible to plants. Soil testing services which include estimates of phosphate buffering reflect its decrease and the consequent increase in fertilizer effectiveness. We propose a simple test to reflect the rate of decline in effectiveness with time. Conclusions Managing phosphate applications using soil tests alone underestimates phosphate status and leads to over application of phosphate. It is necessary to also include estimates of the change in phosphate buffering and the change in the rate of decline in effectiveness with time. A simple way to estimate the rate of decline is suggested.